2010
DOI: 10.1530/eje-09-0930
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone suppression test predicts later development of an impaired adrenal function after a 14-day course of prednisone in healthy volunteers

Abstract: Background: Suppression of the adrenal function after glucocorticoid treatment is common, potentially dangerous, and unpredictable. Identification of patients at risk is of clinical importance. We hypothesized that the dexamethasone suppression test predicts the development of corticosteroidinduced impaired adrenal function. Methods: We included 39 healthy male volunteers. After a 1-mg ACTH test, all participants underwent an overnight 0.5-mg dexamethasone suppression test. Participants then took prednisone, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Other plausible gene loci include those coding for the glucocorticoid receptor or the enzyme 11β-HSD. The response to glucocorticoids varies considerably among individuals and this may also affect susceptibility to glucocorticoid-induced adrenal insufficiency, as demonstrated by the low-dose dexamethasone suppression test (62). At present, polymorphisms in the gene loci encoding the glucocorticoid receptor as well as 11β-HSD are leading candidate genes to account for the large variation in glucocorticoid response (63).…”
Section: Biomarkers and Genotypesmentioning
confidence: 99%
“…Other plausible gene loci include those coding for the glucocorticoid receptor or the enzyme 11β-HSD. The response to glucocorticoids varies considerably among individuals and this may also affect susceptibility to glucocorticoid-induced adrenal insufficiency, as demonstrated by the low-dose dexamethasone suppression test (62). At present, polymorphisms in the gene loci encoding the glucocorticoid receptor as well as 11β-HSD are leading candidate genes to account for the large variation in glucocorticoid response (63).…”
Section: Biomarkers and Genotypesmentioning
confidence: 99%
“…However, individual variation in HPA axis function after GC withdrawal can be observed and it may be caused by individual variation in sensitivity towards GCs. It has been demonstrated that the risk of suppressed adrenal function after a seven-day prednisone treatment is increased in subjects who have a low cortisol level after a dexamethasone suppression test [ 84 ]. Individual differences in GC sensitivity are important in evaluating a patient’s risk of developing GC-induced adrenal insufficiency.…”
Section: Effects Of Glucocorticoids Therapy On the Hypothalamus–pimentioning
confidence: 99%
“…Short courses (<2 weeks) of high dose glucocorticoids are usually associated with a swift recovery of adrenal function,183738 although cases of GI-AI lasting more than seven to 14 days have been described 31394041424344. The possible exception to this is in patients who receive frequent short glucocorticoid courses, as in the treatment of asthma or chronic obstructive pulmonary disease and during emetogenic chemotherapy.…”
Section: Factors Affecting Likelihood Of Glucocorticoid Induced Adrenal Insufficiencymentioning
confidence: 99%
“…Inter-individual variability in the sensitivity of the HPAA to exogenous glucocorticoids has been observed 44128129. For example, higher cortisol after administration of dexamethasone was associated with an inadequate response to the low dose ACTH stimulation test after a 14 day course of prednisolone in healthy volunteers 44.…”
Section: Factors Affecting Likelihood Of Glucocorticoid Induced Adrenal Insufficiencymentioning
confidence: 99%
See 1 more Smart Citation